2003
DOI: 10.1614/0043-1745(2003)051[0430:sahokk]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Surfactants affect herbicides on kochia (Kochia scoparia) and Russian thistle (Salsola iberica)

Abstract: The effects of surfactants on retention, absorption, and efficacy were determined for bromoxynil, 2,4-D amine, and glyphosate on kochia and Russian thistle. Bromoxynil, 2,4-D amine, and glyphosate retention were similar for both species. Surfactants improved spray retention on kochia and Russian thistle compared with spray mixtures without surfactant. Herbicides mixed with allinol 810-60 surfactant were generally retained better than with MON 0818, oxysorbic 20, or R-11 surfactant. Bromoxynil phytotoxicity was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 17 publications
0
28
1
Order By: Relevance
“…Several studies have reported reduced efficacy of POST herbicides as weed height increases (Waite et al 2013). In this study, a sharp decline in the efficacy of fluthiacetmethyl plus mesotrione for controlling 20-cm-tall glyphosate-resistant kochia was observed, which might be due to morphological or physiological adaptations such as narrow, hairy, and waxy leaves (Harbour et al 2003). The pubescence of kochia leaves and crystalline epicuticular wax interrupts the herbicide droplets above the cuticle and prevents contact with epicuticular surface for absorption into plant-system (de Ruiter et al 1990; Wirth et al 1991).…”
Section: Kochiamentioning
confidence: 58%
“…Several studies have reported reduced efficacy of POST herbicides as weed height increases (Waite et al 2013). In this study, a sharp decline in the efficacy of fluthiacetmethyl plus mesotrione for controlling 20-cm-tall glyphosate-resistant kochia was observed, which might be due to morphological or physiological adaptations such as narrow, hairy, and waxy leaves (Harbour et al 2003). The pubescence of kochia leaves and crystalline epicuticular wax interrupts the herbicide droplets above the cuticle and prevents contact with epicuticular surface for absorption into plant-system (de Ruiter et al 1990; Wirth et al 1991).…”
Section: Kochiamentioning
confidence: 58%
“…Leaves have a crystalline epicuticular wax structure similar to that of kochia, which was suggested as a possible reason for the similar herbicide absorption between species (Harbour et al 2003).…”
Section: Response To Herbicides and Other Chemicalsmentioning
confidence: 98%
“…Leaves are generally pubescent with crystalline epicuticular wax, which may result in suspended herbicide spray droplets above the cuticle and, consequently, reduced absorption (Harbour et al 2003). Kochia growth stage and herbicide dose also markedly affect herbicide efficacy.…”
Section: Response To Herbicides and Other Chemicalsmentioning
confidence: 99%